2005
DOI: 10.1152/ajplung.00150.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione restores collagen degradation in TGF-β-treated fibroblasts by blocking plasminogen activator inhibitor-1 expression and activating plasminogen

Abstract: restores collagen degradation in TGF-␤-treated fibroblasts by blocking plasminogen activator inhibitor-1 expression and activating plasminogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 76 publications
0
48
1
Order By: Relevance
“…u-PAR can regulate plasminogen-induced apoptosis of fibroblasts through enhancement of cell surface plasminogen activation upon ligation with u-PA, an effect blunted by TGF␤-mediated induction of PAI-1 (26). We have shown that repletion of glutathione, a potent antioxidant, in TGF␤-treated fibroblasts restores the TGF␤-induced collagen degradation defect (61) and, furthermore, that the effect of glutathione on overall collagen degradation in TGF␤-treated fibroblasts is a consequence of regulation of plasminogen activation (61).…”
Section: Discussionmentioning
confidence: 80%
“…u-PAR can regulate plasminogen-induced apoptosis of fibroblasts through enhancement of cell surface plasminogen activation upon ligation with u-PA, an effect blunted by TGF␤-mediated induction of PAI-1 (26). We have shown that repletion of glutathione, a potent antioxidant, in TGF␤-treated fibroblasts restores the TGF␤-induced collagen degradation defect (61) and, furthermore, that the effect of glutathione on overall collagen degradation in TGF␤-treated fibroblasts is a consequence of regulation of plasminogen activation (61).…”
Section: Discussionmentioning
confidence: 80%
“…It is known that GSH plays a prominent role in immune responses (17,23,29,38), extracellular matrix remodeling (50,56), and in inflammatory responses (43). Chronic bronchopulmonary infection is a hallmark feature in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, fibroblast-mediated release of HGF was greatly potentiated by the presence of plasminogen in the culture environment. Fibroblasts are known to produce plasminogen activators (35)(36)(37). Second, exposure of ECM to reagent plasmin leads to HGF release.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of radiolabel released into the media after 6 h of incubation was measured. The addition of plasminogen or cells alone released small amounts of radiolabel from the ECM ( Figure 2A); however, when NIH3T3 cells (which are known to produce uPA [35][36][37]) and plasminogen were combined, the release of radioactivity from the matrices increased in a plasminogen dosedependent fashion. Extending the incubation time of cells plus 10 g/ml plasminogen to 24 h caused release of greater than 90% of the bound radioactivity (data not shown).…”
Section: Release Of 125 I-hgf From Ecm By Nih3t3 Cellsmentioning
confidence: 99%